We would have told each other everything : a novel - Hermann, Judith, 1970- (FSG Originals / Farrar, Straus and Giroux, 2026)
"A wise and subtle work from one of Germany's greatest living authors on the refractive power of memory, art, and how we live in the lives of others"-- Provided by publisher.